Beiträge zur Taxonomie und Faunistik der paläarktischen Trauermücken (Diptera, Sciaridae). Teil I. - Die Stroblschen Sciaridentypen des Naturhistorischen Museums des Benediktinerstiftes Admont. - Menzel, Frank (Contributions to Entomology = Beiträge zur Entomologie, 1992)
The types of 21 species of Sciaridae (Diptera, Nematocera) described by Strobl and housed in the 'Naturhistorisches Museum des Benediktinerstifts Admont' are revised. 5 new combinations and 14 new synonyms have been found. 19 species have been redescribed and figured. Sciara incana Strobl, 1910, is a nomen dubium, Trichosia nigriclava Strobl, 1893, Nowakia simillima Strobl, 1910 and Nowakia scatopsiformis Strobl, 1893 do not belong to the Sciaridae. Nomenclatural Actsbrevifurcata (Strobl, 1910) (Bradysia), comb. n. hitherto Cratyna brevifurcataleucotricha Tuomikoski, 1960 (Lycoriella (Bradysiopsis)), syn. n. of Lycoriella (Bradysiopsis) nigripes (Strobl, 1898)nigripes Strobl, 1898 (Lycoriella (Bradysiopsis)), Lectotype; stat. nov.; comb. n. described as Sciara quinquelineata var. nigripeslongicornis Antonova, 1975 (Lycoriella (Hemineurina)), syn. n. of Lycoriella (Hemineurina) morenae (Strobl, 1900)morenae (Strobl, 1900) (Lycoriella (Hemineurina)), comb. n. hitherto Sciara morenaespeciosissima Strobl, 1898 (Lycoriella (Hemineurina)), comb. n. hitherto Sciara speciosissimalongiseta Bukowski & Lengersdorf, 1936 (Neosciara), syn. n. of Lycoriella (Hemineurina) morenae (Strobl, 1900)obtusicauda (Strobl, 1900) (Plastosciara (Peyerimhoffia)), Lectotype; comb. n. hitherto Sciara obtusicaudahirsutissima Strobl, 1895 (Sciara), Lectotype now a synonym of Trichosia (Leptosciarella) coarctata (Winnertz, 1867)interrupta Strobl, 1895 (Sciara), syn. n. of Trichosia (Leptosciarella) elegans (Winnertz, 1867)nitidissima Strobl, 1880 (Sciara), syn. n. of Xylosciara (Xylosciara) lignicola (Winnertz, 1867)defecta Strobl, 1910 (Sciara elegans var.), syn. n. of Trichosia (Leptosciarella) scutellata (Staeger, 1840)nigrithorax Strobl, 1898 (Sciara flavipes var.), syn. n. of Phytosciara (Prosciara) flavipes (Meigen, 1804)minor Strobl, 1898 (Sciara frauenfeldi var.), Lectotype; syn. n. of Sciara militaris Nowicki, 1868varicornis Strobl, 1910 (Sciara ingrata var.), syn. n. of Bradysia aprica (Winnertz, 1867)alpujarrensis Strobl, 1900 (Sciara quinquelineata var.), Lectotype; syn. n. of Lycoriella (Bradysiopsis) nigripes (Strobl, 1898)nevadensis Strobl, 1900 (Sciara thomae var.), Lectotype; syn. n. of Scythropochroa quercicola (Winnertz, 1869)jugicola Strobl, 1898 (Trichosia), Lectotype; syn. n. of Trichosia (Leptosciarella) hirtipennis (Zetterstedt, 1838)